Prediction of post-traumatic stress disorder based on perceived anxiety caused by coronavirus in nurses - Seyed Mojtaba Aghili; Azadeh Rahat Ramroudi (فصلنامه ابن سینا)
Background and aims: The release of covid-19 has created a global health emergency in less than a few months around the world. The aim of this study was to predict Post-Traumatic Stress Disorder (PTSD) based on perceived anxiety caused by coronavirus in nurses of a hospital in Quchan city, Iran in 2020. Methods: In this descriptive correlational study, 100 nurses of a hospital in Quchan city were selected by convenience sampling method, and then Corona Disease Anxiety Scale (CDAS) and PTSD CheckList (Civilian Version) (PCL-C) were responded by them. Data were analyzed using descriptive statistics, Pearson correlation coefficient, and stepwise regression analysis. Results: The results showed that anxiety caused by Covid-19 was able to predict PTSD in nurses (p<0.001). The highest values for predicting of PTSD in nurses were related to physical symptoms and psychological symptoms, respectively. Conclusion: The coronavirus anxiety reduction techniques are recommended for nurses to reduce PTSD.